Kebijakan Pemerintah Republik Indonesia dan Hukum Islam Mengenai Poligami: Sebuah Kajian Perbandingan - Khoirul A. Harahap (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
Based on Law No. 1 of 1974 about Marriage, the Government of Indonesia has determined to adhere to the principle of monogamy in terms of marital arrangements. However, the Government of Indonesia does not decline polygamy opportunity for its citizens who wish to marry more than one person with some determined conditions and procedures. In the perspective of Islamic law, polygamy is permissible, but not mandatory and recommended. The law of polygamy in Islamic law follows the circumstances and conditions of someone who wants to practice polygamy. This study seeks to analyze and compare the Government of Indonesia policy and Islamic law in terms of marriage, especially regarding the reasons, conditions, and procedures for polygamy.